2001
DOI: 10.1111/j.1348-0421.2001.tb02609.x
|View full text |Cite
|
Sign up to set email alerts
|

Cluster Analysis of Human and Animal Pathogenic Microsporum Species and Their Teleomorphic States, Arthroderma Species, Based on the DNA Sequences of Nuclear Ribosomal Internal Transcribed Spacer 1

Abstract: Abstract:We performed a cluster analysis of human and animal pathogenic Microsporum species and their teleomorphic states, Arthroderma species, including A. otae-related species (M. canis, M. audouinii, M. distortum, M. equinum, M. langeronii, and M. ferrugineum) and M. gypseum complex (A. fulvum, A. gypseum, and A. incurvatum) using DNA sequences of nuclear ribosomal internal transcribed spacer 1 (ITS1). The dendrogram showed the members of A. otae-related species to be monophyletic and to construct an extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…The study revealed that Nannizzia species had distinct restriction patterns and this matched with subsequent ITS [2] and multilocus studies [3]. Later, phylogenetic studies [55,56] all demonstrated highly concordant topologies of trees, being largely insensitive to strain and taxon sampling effects. Nannizzia aenigmaticum was published separately as an etiologic agent of tinea corporis [13].…”
Section: Discussionsupporting
confidence: 57%
“…The study revealed that Nannizzia species had distinct restriction patterns and this matched with subsequent ITS [2] and multilocus studies [3]. Later, phylogenetic studies [55,56] all demonstrated highly concordant topologies of trees, being largely insensitive to strain and taxon sampling effects. Nannizzia aenigmaticum was published separately as an etiologic agent of tinea corporis [13].…”
Section: Discussionsupporting
confidence: 57%
“…In the present study, we only include a single clinical specimen. Microsporum gypseum is a complex comprising several species ( Arthroderma gypseum and A. incurvatum ) 11 and to our knowledge there are few reports studying this complex by molecular analysis of ITS regions 18–20 . Microsporum canis , M. ferrugineum and Microsporum CHUS‐126‐02 could not be differentiated by means of these procedures.…”
Section: Discussionmentioning
confidence: 99%
“…[21] studied with PCR fingerprinting and amplified fragment length polymorphism (AFLP) different strains of Microsporum species and concluded that M. canis , M. ferrugineum and M. audouinii have ITS sequences very similar to A. otae and the set of these three species is conspecific. Makimura et al [20] also carry out a cluster analysis based on the ITS region and reported several strains of the A. otae complex (including M. canis and M. ferrugineum ) presented an extremely closely related cluster with a very similar ITS sequence. Future sequencing studies of other DNA regions are necessary.…”
Section: Discussionmentioning
confidence: 99%
“…This strain also formed primers 18SF1 (5'-AGG TTT CCG TAG GTG AAC CT-3') and 58SR1 (5'-TTC GCT GCG TTC TTC ATC GA-3') as described by Makimura et al (2001). The thermal cycling profile was an initial denaturation step at 94℃ for 5 min, followed by 25 cycles of 94℃ for 1 min, 60℃ for 15 s and 72℃ for 15 s, and a single final extension step at 72℃ for 10 min.…”
Section: Resultsmentioning
confidence: 99%